2018
DOI: 10.1071/ch18347
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of FtsZ Crystal Structures Towards a New Target for Antibiotics

Abstract: The bacterial cell division protein FtsZ is conserved in most bacteria and essential for viability. There have been concerted efforts in developing inhibitors that target FtsZ as potential antibiotics. Key to this is an in-depth understanding of FtsZ structure at the molecular level across diverse bacterial species to ensure inhibitors have high affinity for the FtsZ target in a variety of clinically relevant pathogens. In this study, we show that FtsZ structures differ in three ways: (1) the H7 helix curvatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…The site shows only a relatively limited conservation across FtsZs of different bacterial species. As a result, variations in the amino-acidic composition and site accessibility could account, at least in part, for the observed differences in the susceptibility Antibiotics 2020, 9, 69 4 of 28 of FtsZ from different bacterial strains to the same inhibitor or to inhibitors belonging to similar chemotypes [11]. While this variability may pose a challenge for the development of broad-spectrum antimicrobials, the specificity of this area and its structural divergence from the corresponding portions of tubulin may rule out potential toxicity concerns of inhibitors targeting the GTP-binding site, which shows a high homology between the two proteins.…”
Section: Interdomain Sitementioning
confidence: 99%
See 2 more Smart Citations
“…The site shows only a relatively limited conservation across FtsZs of different bacterial species. As a result, variations in the amino-acidic composition and site accessibility could account, at least in part, for the observed differences in the susceptibility Antibiotics 2020, 9, 69 4 of 28 of FtsZ from different bacterial strains to the same inhibitor or to inhibitors belonging to similar chemotypes [11]. While this variability may pose a challenge for the development of broad-spectrum antimicrobials, the specificity of this area and its structural divergence from the corresponding portions of tubulin may rule out potential toxicity concerns of inhibitors targeting the GTP-binding site, which shows a high homology between the two proteins.…”
Section: Interdomain Sitementioning
confidence: 99%
“…The 2,6-difluoro substitution was proven to increase activity. The benzamide group interacts via hydrogen bonds with specific residues in the T7 loop of FtsZ (e.g., Val207 and Leu209 in S. aureus) which are conserved across different species [11]; • An alkylenoxy or alkylenamine linker region of different lengths; • A variable terminal region including either an alkyl chain (functionalized or non-functionalized) or a heterocyclic moiety, which is accommodated in a narrow, deep, and hydrophobic cavity inside the interdomain cleft. In general, affinity is promoted by the possibility to form additional interactions and is strongly limited by the hydrophobic nature and steric constraints of the binding site.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although FtsZ has minimal sequence similarity with tubulin, there are several regions that are highly similar in both proteins. Tubulin and FtsZ share only ∼10–18% sequence identity, yet both exhibit structural homology ( de Pereda et al, 1996 ; Kusuma et al, 2019 ), suggesting convergent evolution ( van den Ent et al, 2001 ; Battaje and Panda, 2017 ). Sequence alignment of FtsZ, α-tubulin and β-tubulin demonstrated that the T1 loop (common glycine), T4 loop (with the tubulin signature motif), T5 loop (common prolines), T6 loop (common asparagine), and T7 loop (common asparagine and aspartate) show high sequence identity.…”
Section: Similarities and Differences Between Tubulin And Ftszmentioning
confidence: 99%
“…This allows for FtsZ inhibitors with selective activity against bacterial cell division. One major structural difference is an interdomain cleft adjacent the H7-core helix that separates the two subdomains of FtsZ, a feature which is not present in tubulin [10]. Additionally, the linker that follows the C-terminal globular domain of FtsZ (also known as the disordered region) is thought to play a role in tethering and maintenance of protein-protein interactions that are essential for bacterial cell division [4].…”
Section: Introductionmentioning
confidence: 99%